Panitumumab in metastatic colorectal cancer. Issue 7 (July 2013) - Hocking, Christopher M; Townsend, Amanda R; Price, Timothy J
Increasing chemotherapeutic and targeted drug options has led to improved overall survival in metastatic colorectal cancer. Panitumumab is a fully humanized monoclonal antibody that binds to the EGF receptor and inhibits downstream cell signaling with net effects of inhibition of tumor growth, induction of apoptosis and inhibition of angiogenesis. Panitumumab leads to improved response rate and progression-free survival when used in combination with chemotherapy and as monotherapy in metastatic colorectal cancer. This benefit is limited to patients who have non-mutated KRAS tumors, and regulatory agencies worldwide have restricted panitumumab to this patient population. Rash is a common side effect of panitumumab, and prophylactic skin treatments are advised. The optimal use of panitumumab is evolving and will become further defined with results of upcoming clinical trials and improved identification of biomarkers predicting benefit of this class of drugs